Reprogramming axial ligands facilitates the self-assembly of a platinum(iv) prodrug: overcoming drug resistance and safer in vivo delivery of cisplatin. Issue 66 (31st July 2018) - Fang, Tao; Ye, Zhijian; Wu, Jiaping; Wang, Hangxiang
Abstract : We herein reprogrammed axial ligands of platinum(iv ) prodrugs, conferring the constructed prodrug entities with the ability to self-assemble in aqueous solution. Abstract : We herein reprogrammed axial ligands of platinum(iv ) prodrugs, conferring the constructed prodrug entities with the ability to self-assemble in aqueous solution. Further cloaking of the PEG chain with Pluronic surfactant makes this nanoassembly (termed Pt(iv )-NP) suitable for systemic injection. Notably, Pt(iv )-NP significantly alleviated the toxicity of the parent cisplatin drug in vivo while preserving the pharmacological activity.